3D printing technology for thermal application: a brief review - Rajan, Kumaresan; Mahendran, Samykano; K., Kadirgama; D., Ramasamy; Ngui, Wai Keng; Adarsh Kumar, Pandey (Akademi Baru, 2021)
3D printing is an emerging technology to construct complex geometry by a layer-by-layer technique by using a 3-dimensional model. Mass customization, freedom of design, and wastage minimization are the main advantages of Additive Manufacturing (AM) or 3D printing. AM process is currently used in many sectors worldwide, such as automotive, aerospace, agriculture, medical, electronics, and other household products. At the same time, the usage of the AM technique is limited in large production sectors due to the limitation of the materials and properties of the produced parts. In this review, the different methods of 3D printing, the materials used in different processes, various fields of applications, and the properties of the different approaches were discussed. Also, the effect of process parameters such as layer thickness, nozzle temperature, platform temperature, printing speed, extruding rate, and layer height in 3d printing was reviewed. This will be helpful for further development of 3D printed product quality and applications in various sectors.